These are the things that sit with us : Voices from Bonteheuwel, Langa and Worcester = Izinto ezisiSingqala kuthi : Amabali okwenyani asuka kubantu abahlala eBonteheuwel, KwaLanga naseWorcester = Hierdie is die goed wat aan ons kleef : Stemme uit Bonteheuwel, Langa en Worcester - Pumla Gobodo-Madikizela; Gobodo-Madikizela, Pumla; Bubenzer, Friederike; Oelofsen, Marietjie (Auckland Park, South Africa : Fanele, 2019)
Our country has a complicated history, and this history has affected the present. These Are the Things That Sit With Us makes visible the undocumented everyday experiences that shaped the lives of ordinary South Africans during the country's brutal and painful past. It is a record of things that 'sit' within all of us. By sharing their memories, the storytellers map the scope of the wider, more difficult conversation about the meaning of justice and the missing parts of the discourse of reconciliation in South Africa. It creates a space for a conversation about South Africa's history and what it means to talk to and to hear the other within the context of this history. In publishing each story in isiXhosa, Afrikaans and English, we hope that the book will stimulate conversation among South Africans across languages. -- Publisher's description.
"Voices from Bonteheuwel, Langa and Worcester = Amabali okwenyani asuka kubantu abahlala e Bonteheuwel, KwaLanga nase Worcester = Stemme uit Bonteheuwel, Langa en Worcester" - Title page.
Fanele is an imprint of Jacana Media - Verso of title page.
Parallel texts in English, Afrikaans, and Xhosa.
Keywords: South Africa -- Social conditions; South Africa -- Race relations; South Africa -- Politics and government; South Africa -- History; District Six (Cape Town, South Africa)